THE PROBLEM OF CORRUPTION LAW ENFORCEMENT THAT CAUSES STATE LOSSES SINCE THE CONSTITUTIONAL COURT OF THE REPUBLIC OF INDONESIA NUMBER 25 / PUU-XIV / 2016 DECISION - Muhammad Zaki; Tofik Y Chandra; Hedwig Adianto Mau (Transpublika Publisher, 2022)
are increasingly widespread, so that the boundaries of the characteristics of acts of corruption and the characteristics of acts that are not corrupt but characterized by very detrimental to the state and society become difficult to distinguish, and lead to uncertainty about how to formulate groups. his crime. This research is a normative legal research that uses primary and secondary legal sources with library research collection techniques through legislation approach, historical approach and case approach. The results obtained are the legal considerations of the judges of the Constitutional Court of the Republic of Indonesia in the Decision of the Constitutional Court Number 25/PUU/XIV/2016 in Article 2 Paragraph (1) and Article 3 of Law Number 20 of 2001 concerning Eradication of Criminal Acts of Corruption in Decision Number 25/ PUU-XIV/2016 which grants the abolition of the phrase “can” is to create legal certainty for the State Civil Apparatus (ASN) regarding discretionary policies or decisions or the implementation of the Ermessen freies principle which is criminalized as a criminal act of corruption because it is detrimental to state finances.